(untitled) (Annals of Medical Research, 2021)
Aim: To evaluate the outcomes after bilateral implantation of a new trifocal intraocular lens (IOL).Materials and Methods: The study included patients with visually significant cataract that underwent bilateral implantation of the Acriva Trinova Sinusoidal Trifocal IOL. The preoperative corrected distance visual acuity (CDVA) and postoperative uncorrected distance visual acuity (UDVA), CDVA, uncorrected intermediate (UIVA) and near visual acuities (UNVA) along with manifest refractions were assessed at 1 month and 6 months after cataract surgery. The defocus curve and contrast sensitivity (CS) were evaluated at the 6th month visit. Patient satisfaction and incidence of dysphotopic symptoms were assessed. Results: The study enrolled a total of 60 eyes of 30 patients, 10 males and 20 females aged 61.78± 8.73 years (range, 45 to 78 years). 90% of the patients (n: 27) achieved a binocular UIVA of 0.1 LogMAR or better at the 6-month visit while, 96.7% (n:29) patients had a binocular UNVA of 0.1 LogMAR or better in the same postoperative visit. The CS results were within the the range of normality at 6 months post-surgery. 6.7% of patients reported marked halo around light sources and 3.3% reported glare that interferes with nighttime driving. 96.6% of the patients reported spectacle independence for all distances and rated their visual function and quality satisfactory at all distances. Conclusion: Bilateral implantation of the Acriva Trinova Sinusoidal Trifocal IOL seems to provide effective restoration of visual function at all distances after cataract surgery in the majority of patients. Contrast sensitivity results and low incidence of dysphotopic phenomena might be associated with high patient satisfaction.